Výzkum v didaktice cizích jazyků II - Jelínková, Jaroslava (Masaryk University Press, 2019)
Title in English: Research in foreign language didactics II. The volume of proceedings is a result of the Specific Research project conducted in 2018 with the registration number MUNI/A/1143/2018 - Research on learning and teaching foreign languages. The contributions present research studies of doctoral students in the field of Foreign Language Didactics at the Faculty of Education of Masaryk University. The studies are written in Czech.